"Tabula Rasa" planning: creative destruction and building a new urban identity in Tehran. Issue 3 (3rd July 2017) - Mehan, Asma
Abstract: The concept of Tabula Rasa, as a desire for sweeping renewal and creating a potential site for the construction of utopian dreams is presupposition of Modern Architecture. Starting from the middle of the 19th century to the first half of the 20th century, Iranian urban and architectural history has been integrated with modernization, and western-influenced modernity. The case of Tehran as the Middle Eastern political capital is the main scene for the manifestation of modernity within it's urban projects that was associated with several changes to the social, political and spatial structure of the city. In this regard, the strategy of Tabula Rasa as a utopian blank slate upon which a new Iran could be conceived "over again" – was the dominant strategy of modernization during First Pahlavi era (1925–1941). This article explores the very concept of constructing a new image of Tehran through the processes of autocratic modernism and orientalist historicism that also influenced the discourse of national identity during First Pahlavi era.